Subjective characteristics of social responsibility and their impact on the accounting process - I.V. Zhyhlei (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Social responsibility within the concept of sustainable development is becoming more common in various aspects of society. The objective of the articles is human relationships, businesses and the state as socially responsible entities, also their impact on the accounting system. The complexity of relations between the state, employers and an individual person lies in a conflict of interests that affect economic, cultural, scientific, social spheres. The participants of these relations are imposed responsibility for their needs, interests, expression, activity and other vital processes that may affect the other entities. After all, every party is specific and unique customer of the performance and behavior of others. In this regard, it is necessary to clarify the concept of responsibility, enterprise, government and society as a whole. The issue of social responsibility was considered on the basis of the available publications of foreign and domestic scientists (philosophers, psychologists, political scientists, sociologists and economists). Through analysis, synthesis, classification, the social responsibility was specified with the help of social and economic rules and laws. Results of the study will serve as a guide to explore the impact of social responsibility in accounting, analytical and strategic activities.